In vitro/vivo Mechanism of Action of MP1102 With Low/Nonresistance Against Streptococcus suis Type 2 Strain CVCC 3928 - Zhao, Fei; Yang, Na; Wang, Xiumin; Mao, Ruoyu; Hao, Ya; Li, Zhanzhan; Wang, Xiao; Teng, Da; Fan, Huan; Wang, Jianhua (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcosis is recognized as a leading infectious disease in the swine industry. Streptococcus suis serotype 2 is regarded as the most virulent species, which threatens humans and pigs health and causes serious economic losses. In this study, in vitro and in vivo multiple effects of MP1102 on multi-drug resistant S. suis was studied for the first time. MP1102 exhibited very high antibacterial activity against S. suis (MIC=0.028-0.228 μM), rapid killing, a longer postantibiotic effect than ceftriaxone, and synergy or additive effect with lincomycin, penicillin, and ceftriaxone (FICI=0.29-0.96). No resistant mutants appeared after 30 serial passages S. suis in the presence of MP1102. Flow cytometric analysis and electron microscopy observations showed that MP1102 destroyed S. suis cell membrane integrity and affected S. suis cell ultrastructure and membrane morphology, including seriously wrinkled surface, intracellular content leakage and cell lysis, establishing a cyto-basis of low/non-resistance form this pathogen. DNA gel retardation and circular dichroism analysis indicated that MP1102 interacted with DNA by binding to DNA and changing the DNA conformation, even leading to the disappearance of the helical structure, which further consolidated the former mechanism basis of low/non-resistance in the way of intraceller target as secondary injury after MP1102 moved across the membrane. At the doses of 2.5-5.0 mg/kg MP1102, the survival of mice challenged with S. suis were 83.3-100%. MP1102 decreased the bacterial translocation in liver, lung, spleen, and blood, inhibited the release of interleukin-1β and tumor necrosis factor-α, and relieved the lung, liver, and spleen from acute injury induced by S. suis. These results suggest that MP1102 may be a novel antimicrobial agent for the therapy of pig streptococcus disease.